Features of cerebral blood flow, cardiac arrhythmias and conduction disturbances in patients with essential hypertension stage II associated with occlusive and stenotic lesions of brachiocephalic arteries. - Vizir, V. A.; Shkolovоy V. V. (Medicni Perspektivi, 2015)
Arterial hypertensionis the most common disease of the cardiovascular system in industrially advanced countries. With the aim to determine the characteristics of cerebral blood flow, disorders of cardiac rhythm and conduction in patients with stage 2 hypertension associated with stenotic and occlusive lesions of brachiocephalic arteries, cerebral blood flow indicators were studied in 87 patients using duplex scanning of extracranial arteries and Holter ECG monitoring. It was established that linear blood flow velocity was considerably decreased in the basins of the internal and common carotid artery; cerebral blood flow asymmetry was present in the course of the internal carotid artery. Evidence-based differences in structure of arrhythmias were revealed by single and paired ventricular extrasystoles, as well as episodes of unstable ventricular tachycardia. All this indicates the progressive decrease of elasticity and tonicity of vessel walls, intensified rigidity and sinuosity of carotid arteries, more severe disorders of cardiac rhythm and conduction in case of simultaneous hypertension and atherosclerotic lesion of brachiocephalic arteries.